STRATEGI DINAS PERHUBUNGAN KOTA PEKANBARU DALAM MENERTIBKANPARKIR ILEGAL DI KOTA PEKANBARU - Feriyanti Barasa; Nur Laila Meilani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The problem of this study includes the illegal parking on the edge of Pekanbaru's public roads caused by a number of things including limited public roadside parking due to provisions for parking, parking officers who use illegal parking locations, lack of coordination between relevant agencies and parking rates that do not in accordance with established regulations. The purpose of this study was to find out and analyze the strategy of the Pekanbaru City Transportation Agency in regulating illegal parking on the edge of Pekanbaru's public roads. This research method uses descriptive qualitative research methods. This research focuses on the strategy in regulating illegal parking using the SWOT analysis.The results of the study indicate that the Department of Transportation in regulating illegal parking on the public road in the form of preventive actions. The focus of this research is the role of the Department of Transportation in responding to the problem of illegal parking, harmful illegal fees, and the number of vehicles parked on the road / sidewalk. The Department of Transportation has taken strict action to get a deterrent effect, in improving parking management efficiency which is one of the effectiveness in improving parking management in Pekanbaru City. The factor that became a supporter in creating the strategy of the Department of Transportation, namely that the Department of Transportation through the UPTD Parking of the City of Pekanbaru did not have a specific strategy in overcoming illegal parking. The recommended strategy used in overcoming illegal parking is to formalize illegal parking officers by providing new parking locations that are strategically located.Keywords: Strategy, Illegal Parking, Parking Control